2020
DOI: 10.1103/physrevlett.125.186401
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Superconductivity and Charge Density Waves in Tantalum Disulfide: Experiment and Theory

Abstract: The coexistence of charge density wave (CDW) and superconductivity in tantalum disulfide (2H-TaS 2) at low temperature is boosted by applying hydrostatic pressures to study both vibrational and magnetic transport properties. Around P c , we observe a superconducting dome with a maximum superconducting transition temperature T c ¼ 9.1 K. First-principles calculations of the electronic structure predict that, under ambient conditions, the undistorted structure is characterized by a phonon instability at finite m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…Group V-b TMDs tend to exhibit competition/interplay between the charge density wave (CDW) phases and superconducting phases [346,347] . In both NbSe2 and TaS2, it is found that applying compressive pressure favors the formation of the superconducting phase [348,349] . Understanding the interplay between these two phases in these materials may elucidate the unconventional superconductivity in these systems.…”
Section: D Superconductorsmentioning
confidence: 99%
“…Group V-b TMDs tend to exhibit competition/interplay between the charge density wave (CDW) phases and superconducting phases [346,347] . In both NbSe2 and TaS2, it is found that applying compressive pressure favors the formation of the superconducting phase [348,349] . Understanding the interplay between these two phases in these materials may elucidate the unconventional superconductivity in these systems.…”
Section: D Superconductorsmentioning
confidence: 99%
“…Charge-density waves (CDWs) transition, usually coexisting with Cooper pair condensation in TMDs, was previously reported to have been associated with structural distortions of the lattice sites 5 8 . For instance, CDW effect was found to promote superconductivity in 1T-TaS structure 9 , 10 . Following this, pressure significantly affects superconductivity in this very structure as well: a pressure range of 3-25 GPa gives rise to a superconducting transition temperature (T ) of 5 K. Moreover, there are also studies that give more detailed discussions on the layered structures of TMDs at both ambient and high pressure, for example, WTe was confirmed to superconduct 11 and clearly shown that the van der Waals (vdW) forces play an important role 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, two-dimensional (2D) van der Waals materials have spurred enormous interest due to their unique magnetic properties and potential to develop multi-functional electronics and spintronics devices [1][2][3][4][5]. Among various 2D systems, the family of CrX 3 (X = Cl, Br, and I) has recently been at the center of widespread research in developing high-quality samples, from monolayer to bulk single crystals.…”
mentioning
confidence: 99%